2021
DOI: 10.1002/smtd.202100878
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Controllable Growth NixPy Modified CdS@Ni3S2 Electrodes for Efficient Electrocatalytic and Enhanced Photoassisted Electrocatalytic Overall Water Splitting

Abstract: The rational design and construction of cost‐effective nickel‐based phosphide or sulfide (photo)electrocatalysts for hydrogen production from water splitting has sparked a huge investigation surge in recent years. Whereas, nickel phosphides (NixPy) possess more than ten stoichiometric compositions with different crystalline. Constructing NixPy with well crystalline and revealing their intrinsic catalytic mechanism at atomic/molecular levels remains a great challenge. Herein, an easy‐to‐follow phase‐controllabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…According to the C–C hybrid binding energy at 284.8 eV (Figure 6D), in the calibrated Ti 2p, O 1s, Cd 3 d, and S 2p high‐resolution XPS spectra (Figure 6E–H): the binding energy peaks at around 464.3 and 458.6 eV can be, respectively, attributed to the Ti 2p 1/2 and Ti 2p 3/2 of Ti 4+ in TiO 2 ; [ 55 ] the binding energy peaks at about 530.0, 531.4, and 532.0 eV are related to the crystal lattice oxygen of Ti–O–Ti in TiO 2 and surface adsorbed water and hydroxyl groups, respectively; [ 57 ] the characteristic Cd 3d energy binding peaks located around 405.0 and 412.0 eV, together with the S 2p1/2 and S 2p2/3binding peaks at around 162.7 and 161.5 eV jointly demonstrate the presence of CdS in Ni/TiO 2 @CdS and Ni/TiO 2 @CdS‐300 samples. [ 46 ] Especially, in the Ni 2p high‐resolution spectra (Figure 6I), Ni 3+ and Ni 2+ binding energy peaks located at 875.2, 873.4, 857.6, and 855.8 eV are only found in the Ni/TiO 2 sample, which indicates that partial Ni metals are oxidized during the TiO 2 hydrothermal growth procedure. Associating with the aforementioned analysis results, it is further confirmed the content of Ni 3 S 2 in Ni/TiO 2 @CdS‐300 is very low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the C–C hybrid binding energy at 284.8 eV (Figure 6D), in the calibrated Ti 2p, O 1s, Cd 3 d, and S 2p high‐resolution XPS spectra (Figure 6E–H): the binding energy peaks at around 464.3 and 458.6 eV can be, respectively, attributed to the Ti 2p 1/2 and Ti 2p 3/2 of Ti 4+ in TiO 2 ; [ 55 ] the binding energy peaks at about 530.0, 531.4, and 532.0 eV are related to the crystal lattice oxygen of Ti–O–Ti in TiO 2 and surface adsorbed water and hydroxyl groups, respectively; [ 57 ] the characteristic Cd 3d energy binding peaks located around 405.0 and 412.0 eV, together with the S 2p1/2 and S 2p2/3binding peaks at around 162.7 and 161.5 eV jointly demonstrate the presence of CdS in Ni/TiO 2 @CdS and Ni/TiO 2 @CdS‐300 samples. [ 46 ] Especially, in the Ni 2p high‐resolution spectra (Figure 6I), Ni 3+ and Ni 2+ binding energy peaks located at 875.2, 873.4, 857.6, and 855.8 eV are only found in the Ni/TiO 2 sample, which indicates that partial Ni metals are oxidized during the TiO 2 hydrothermal growth procedure. Associating with the aforementioned analysis results, it is further confirmed the content of Ni 3 S 2 in Ni/TiO 2 @CdS‐300 is very low.…”
Section: Resultsmentioning
confidence: 99%
“…Photoelectrocatalysts have been wildly applied and developed in the energy-related applications. [46] Unfortunately, to our knowledge, although attempts have been strived to construct Ni foam supporting TiO 2 systems, [37,[47][48][49][50][51][52][53][54] the direct fabrication of in situ growth vertically aligned TiO 2 nanorod arrays on Ni foam have never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Therefore, it is urgent to design lowcost but efficient and stable OER electrocatalysts. To this end, transition metal-based electrocatalysts, such as oxides/hydroxides, [9][10][11][12] selenides, [13][14][15][16] sulfides, [17][18][19] and phosphides, [20,21] scheme for the synthetic approach is illustrated in Figure 1. Briefly, unique PB nanotubes are obtained by a solvothermal method, whose morphology differs from those PB polyhedrons in previous literature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in order to improve the utilization efficiency of solar energy, the research on photocatalysts with visible light activity has become one of main research directions in the field of photocatalytic energy conversion. [11][12][13] Introducing defect engineering into heterostructure nanomaterials is an effective method to simultaneously improve their visible light properties and photocatalytic efficiency. [14][15][16] It has been demonstrated that (i) an appropriate amount of defect structures in semiconductor catalyst can be used as electron traps to capture photogenerated electrons, which can promote the effective separation of photogenerated carriers in heterostructures and improve the photocatalytic efficiency; [4,17] (ii) defect structure also benefits the formation of intermediate level and modulation of composite energy levels, which can improve the absorption and excitation of visible light.…”
Section: Introductionmentioning
confidence: 99%